The Two Gentlemen of Verona - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Two Gentlemen of Verona" by William Shakespeare is a comedy believed to have been written between 1589 and 1593. Two best friends from Verona travel to Milan, where their bond faces its greatest test. When both fall for the same woman, one betrays the other through deception and broken vows. The play explores friendship versus love, infidelity, and the foolish behavior of people in love. Featuring a heroine in disguise and Shakespeare's most scene-stealing dog, this early work introduces themes the playwright would revisit throughout his career. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Two_Gentlemen_of_Verona
There is an improved edition of this title, eBook #1509
Release date is 2000-07-01
Keywords: Comedy plays; Verona (Italy) -- Drama; Triangles (Interpersonal relations) -- Drama; Exiles -- Drama